DECELLULARIZED ORGAN-DERIVED TISSUE ENGINEERING SCAFFOLDS (2018)
The presently disclosed subject matter provides for decellularized extracellular matrix (dECM) compositions for reconstructing mucosal tissue of trachea and methods of using the same. In certain embodiments, the composition can be a pre-gel containing dECM derived from tracheal mucosal tissue; a hydrogel obtained by gelling the pre-gel; or a vitrified membrane obtained by drying the hydrogel.